2022
DOI: 10.3390/ijerph192315691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow Restriction Combined with Low-Intensity Resistance Training on Lower-Limb Muscle Strength and Mass in Post-Middle-Aged Adults: A Systematic Review and Meta-Analysis

Abstract: We studied the effect of blood flow restriction (BFR) combined with low-intensity resistance training (LIRT) on lower-limb muscle strength and mass in post-middle-aged adults. The PubMed, OVID, ProQuest, Cochrane Library, EMBASE, Web of Science, and Scopus databases were used to obtain randomized controlled trials, and the effects of BFR and LIRT (BFRt) on muscle strength and mass in adults were examined. The Cochrane risk of bias tool assessed bias in the included trials. The combined effects of BFR and LIRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
1
0
2
Order By: Relevance
“…For special populations, muscle strength is a key factor in promoting mobility, cardiovascular capacity, and performance in daily activities (Obrusnikova et al, 2022). Researchers previously thought that the best approach for improving muscle strength is to perform HL-RT; however, as time progressed, increasing evidence showed that BFR-RT can also effectively improve muscle strength (Takarada et al, 2000;Brandner et al, 2019;Chang et al, 2022). Interestingly, many studies have focused their research objectives on comparing Frontiers in Physiology frontiersin.org the differences in muscle strength gain via BFR-RT and the without vascular occlusion resistance exercise, but the effects of some characteristics of BFR-RT itself on muscle strength gain are generally ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For special populations, muscle strength is a key factor in promoting mobility, cardiovascular capacity, and performance in daily activities (Obrusnikova et al, 2022). Researchers previously thought that the best approach for improving muscle strength is to perform HL-RT; however, as time progressed, increasing evidence showed that BFR-RT can also effectively improve muscle strength (Takarada et al, 2000;Brandner et al, 2019;Chang et al, 2022). Interestingly, many studies have focused their research objectives on comparing Frontiers in Physiology frontiersin.org the differences in muscle strength gain via BFR-RT and the without vascular occlusion resistance exercise, but the effects of some characteristics of BFR-RT itself on muscle strength gain are generally ignored.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy arises when BFR-RT is compared with HL-RT, which is known as the gold standard for increasing muscle strength. For example, some studies have shown that BFR-RT training can produce muscle strength gain similar to HL-RT (Libardi et al, 2015;Centner et al, 2022;Chang et al, 2022), whereas other studies have shown that BFR-RT training leads to less muscle strength gain than HL-RT (Lixandrao et al, 2018;Sieljacks et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yasuda et al [43] showed that low-intensity strength training and BFR-induced functional muscle adaptations are enhanced when combined with HI-RT. Even so, the use of low-intensity BFRT has shown benefits in increasing lower limb strength in rehabilitation processes, especially in middle-aged people [44].…”
Section: Discussionmentioning
confidence: 99%
“…A redução da força muscular de membros inferiores aumenta as chances do surgimento de patologias crônicas, de quedas, do declínio da qualidade de vida e da função corporal, principalmente em idosos (CHANG et al, 2022). Portanto, melhorar a força muscular de membros inferiores é um problema relevante e que deve ser explorado de forma intensiva pelos profissionais da saúde.…”
Section: Treinamento Resistido No Público Idosounclassified
“…As evidências disponíveis até o momento sugerem que o PCI pode induzir adaptações positivas no volume e na força muscular, além de melhora no desempenho físico, em idosos (BAKER et al, 2020;RODRIGO-MALLORCA et al, 2021), com necessidade de uma frequência mínima de três vezes por semana de treinos (CHANG et al, 2022).…”
Section: Treinamento Resistido No Público Idosounclassified